Environmental drivers of denitrification rates and denitrifying gene abundances in channels and riparian areas. Issue 8 (4th August 2017) - Tomasek, Abigail; Kozarek, Jessica L.; Hondzo, Miki; Lurndahl, Nicole; Sadowsky, Michael J.; Wang, Ping; Staley, Christopher
Abstract: Intensive agriculture in the Midwestern United States contributes to excess nitrogen in surface water and groundwater, negatively affecting human health and aquatic ecosystems. Complete denitrification removes reactive nitrogen from aquatic environments and releases inert dinitrogen gas. We examined denitrification rates and the abundances of denitrifying genes and total bacteria at three sites in an agricultural watershed and in an experimental stream in Minnesota. Sampling was conducted along transects with a gradient from always inundated (in‐channel), to periodically inundated, to noninundated conditions to determine how denitrification rates and gene abundances varied from channels to riparian areas with different inundation histories. Results indicate a coupling between environmental parameters, gene abundances, and denitrification rates at the in‐channel locations, and limited to no coupling at the periodically inundated and noninundated locations, respectively. Nutrient‐amended potential denitrification rates for the in‐channel locations were significantly correlated ( α = 0.05) with five of six measured denitrifying gene abundances, whereas the periodically inundated and noninundated locations were each only significantly correlated with the abundance of one denitrifying gene. These results suggest that DNA‐based analysis of denitrifying gene abundances alone cannot predict functional responses (denitrification potential), especially in studies with varying hydrologic regimes. A scaling analysis was performed to develop a predictive functional relationship relating environmental parameters to denitrification rates for in‐channel locations. This method could be applied to other geographic and climatic regions to predict the occurrence of denitrification hot spots. Key Points: Denitrification rates in an agricultural landscape varied temporally and with inundation history Coupling between denitrifying gene abundances, denitrification rates, and environmental parameters varied with inundation history Using a scaling analysis, denitrification rates and environmental parameters were combined to formulate a predictive functional relationship